Facile synthesis of a thermally stable Ce3+:Y3Al5O12 phosphor-in-glass for white LEDs. Issue 37 (7th October 2015) - Huang, Jun; Hu, Xianli; Shen, Jiajian; Wu, Donglin; Yin, Congfei; Xiang, Run; Yang, Cheng; Liang, Xiaojuan; Xiang, Weidong
<x xml:space="preserve">Abstract</x> In this study, we fabricated a transparent Ce:YAG PiG. The luminous efficacy of the PiG-based W-LED reached as high as 134 lm W−1, and the PiG material shows an excellent thermal stability.